Competitiveness indicator in colombia through of multivariable statistics (2019)
The objective of this research is to estimate a competitiveness indicator in Colombia through a factorial methodology of principal components. A competitiveness indicator was estimated presenting significant correlations between chosen variables and according to Kaiser-Mayer-Olkin test, the indicator presents a high degree of usefulness, in terms of correlation, standing out in hierarchical order with the science and technology factors with 0.80; economic affluence with 0.77, geographical condition with 0.75, logistic structure with 0.73, human capital with 0.68, institutional factor with 0.67 and economic dispersion with 0.65. On the other hand, it was found that competitiveness in Colombia is determined by the influx factor of economic activity in the main urban centers of Cundinamarca/Bogotá, Antioquia, Valle and Santander